Occupational Radiation Exposure in Health Care Facilities - Bhatt, Chhavi Raj; Widmark, A; Shrestha, SL; Khanal, T; Ween, B (Kathmandu University Medical Journal, 2013)
Background Radiation, which is used extensively to diagnose and treat human diseases, poses an occupational health risk for the concerned health workers. Personal dosimetry is an important tool to monitor occupational radiation exposures. Objective This study was conducted to reveal and to describe the situation of occupational radiation exposure monitoring among staffs in different health care facilities in Nepal. Methods A cross-sectional study was performed among the 35 Health Care Facilities. Information about types and number of X-ray procedures performed, types and number of personnel involved, workload and the availability of personal dosimetry service were collected. Results Six Health Care Facilities had personal dosimetry service available for a total of 149 personnel. Of a total of nearly one million X-ray procedures performed in the 35 Health Care Facilities in 2007, 76 % was performed by non-monitored personnel. The majority of the facilities performing high dose procedures, like catheterisation, angiography and intestinal barium procedures did not offer personal dosimetry for the involved personnel. Conclusion There are a limited number of personnel being monitored with personal dosimetry. There are no regulatory dose limits for occupationally exposed staff. Thus, there is an urgent need to establish a national radiation protection authority to regulate the use of radiation in Nepal. Kathmandu University Medical Journal | VOL.10 | NO. 3 | ISSUE 39 | JUL- SEP 2012 | Page 48-51 DOI: http://dx.doi.org/10.3126/kumj.v10i3.8019